LEARNING GOAL ORIENTATION SISWA DITINJAU DARI KETERLIBATAN ORANG TUA DAN DUKUNGAN GURU - Laurensius Laka; Ignasius En Gedi Agung Purnomo (Jurnal Pelayanan Pastoral, 2025)
Efforts to enhance the quality of Indonesian human capital were primarily pursued through education. However, the Indonesian education system continued to face a range of interrelated challenges. Discussions concerning educational quality were often linked to external factors affecting students, whereas the quality of learning outcomes did not solely depend on such external influences, but was also shaped by various complex internal factors within the students themselves. This study aimed to analyse the influence of parental involvement and teacher support on the learning goal orientation (LGO) of students at SMPK Santa Maria II Malang. The research employed a survey method, characterised by selecting a sample from a single population and utilising a questionnaire as the primary data collection instrument. The sample comprised 230 students out of a total population of 574. Statistical analysis was conducted using SPSS software with multiple regression techniques. The results indicated that the correlation coefficient between the independent and dependent variables was 0.610, which could be interpreted as a strong relationship. In terms of causality, the simultaneous regression analysis yielded a significance value (Sig.F) of 0.001 (< 0.05), indicating that the regression model was suitable for predicting students’ LGO. Furthermore, the partial regression results demonstrated that both parental involvement and teacher support significantly affected students’ LGO, as evidenced by each variable’s Sig.t value of 0.001 (< 0.05). Therefore, it was concluded that the hypotheses – both simultaneous and partial – were all supported by the data.